Development of Web-Based ICT Learning System at SMP YAPI AL-HUSENI - Premitasari, Marisa; Rakhmat, Galih Ashari; Hadiwibowo, Wirawan; Arefa, Zalfa Tsana; Alwamahaib, Zulfa Sulthany; Rafid, Rayhan Alea; Ibrahim, Farrel Adi (Institut Teknologi Nasional, Bandung, 2024)
ICT, shorten for Information Communication and Technology has been spread to many aspect. One of them were Education System. This project focuses on the development of an ICT learning system in junior high school level at SMP YAPI AL-HUSENI, with a web-based platform. The objective is to enhance the learning experience for students by leveraging the capabilities of web technologies. The system aims to provide an interactive and accessible platform for both students and teachers, facilitating efficient communication and the delivery of educational content. By incorporating web-based features, such as online resources, collaborative tools, and interactive assessments, the ICT learning system strives to create an engaging and dynamic environment for students to acquire essential digital skills. The development process includes designing a user-friendly interface, implementing robust functionalities, and ensuring scalability for future enhancements. Through this initiative, SMP YAPI AL-HUSENI aims to embrace modern educational methodologies and prepare students for the evolving demands of the digital age.